Developing learning skills through game-based learning in complex scenarios: A case in undergraduate logistics education - Ernesto Pacheco-Velazquez; Virginia Rodés; David Salinas-Navarro (OmniaScience, 2024)
This study investigates the impact of game-based learning (GBL), an increasingly popular educational approach, on the development of self-directed learning (SDL) skills in complex scenarios, particularly in undergraduate logistics education. A key component of the three year study is LOST (Logistics Education Simulator), a serious game platform, deployed in an undergraduate engineering course in Mexico. An extensive literature review was carried out using Scopus to examine recent works published between 2019 and 2024, providing a state-of-the-art overview of the field. Subsequently, a survey based on the scale created by Fisher, King, and Tague (2001), known for its extensively evaluated internal consistency, revealed five distinct factors of self-directed learning. The findings underscore that the LOST platform significantly enhances self-directed learning, promoting the development of Self-management Skills, Openness to Learning Opportunities, Initiative and Independence in Learning, Self-concept as an Effective Learner, and Love of Learning. The students demonstrated a significant increase in their perception of these skills over the course of the study, highlighting the effectiveness of GBL in promoting such learning skills. These findings highlight the multidimensional nature of learning skills that can be fostered through GBL. The study concludes by discussing the vital role of GBL in complex scenarios, particularly in enhancing the development of self-directed learning skills in undergraduate logistics education.